Interatrial dyssynchrony on tissue Doppler imaging predicts progression to chronic atrial fibrillation in patients with non-valvular paroxysmal atrial fibrillation. Issue 12 (5th March 2009) - Sakabe, K; Fukuda, N; Fukuda, Y; Morishita, S; Shinohara, H; Tamura, Y
Abstract : Objective: To determine prospectively whether interatrial dyssynchrony detected by tissue Doppler imaging (TDI) is useful for predicting the progression to chronic atrial fibrillation (CAF) in patients with non-valvular paroxysmal AF (PAF). Methods: Thirty-seven patients with non-valvular PAF were prospectively followed after echocardiography. The interval of time from initiation of the P wave on the electrocardiogram (ECG) until the beginning of the late diastolic TDI signal at the lateral border of the mitral annulus (P-A′(M)) and the tricuspid annulus (P-A′(T)) was measured. Interatrial dyssynchrony was defined as the difference between the P-A′(M) and P-A′(T) intervals (A′(M)-A′(T)). The study endpoint was the onset of CAF (>6 months). Results: During a follow-up period of 28 (SD 23) months, eight patients developed CAF. Compared with those without CAF, the patients who developed CAF had a significantly lower atrial systolic mitral (A′(M)) (7.7 (1.7) vs 10.7 (2.9) cm/s, p<0.01) and tricuspid (A′(T)) (12.9 (3.5) vs 16.6 (5.1) cm/s, p<0.05) annular tissue Doppler velocity, as well as a longer A′(M)-A′(T) interval (47 (13) vs 24 (10) ms, p<0.0001). Kaplan–Meier analysis, using cut-off values determined by analysis of receiver-operating characteristics curves, revealed that progression to CAF was significantly more frequent when the A′(M)-A′(T) interval was ⩾34 ms (p<0.01), the A′(M) velocity was ⩽9 cm/s (p<0.05) and the A′(T) velocity was ⩽16 cm/s (p<0.05). Conclusions: This prospective study suggests that non-valvular PAF patients with a high risk of developing CAF have "interatrial dyssynchrony" and "atrial systolic dysfunction" on atrial TDI.